Green Chemistry Strategies for Mitigating Microplastic Pollution in Aquatic Environments - Samuel, Humphrey; Makong, Francis-Dominic; Ori, Merit (CV. Science Tech Group, 2024)
Microplastic pollution poses a growing threat to aquatic ecosystems. This review explores green chemistry strategies for mitigating this issue. The focus is on preventing microplastic generation at the source. Strategies include designing plastic products for reusability and recyclability, developing biodegradable plastics, and utilizing alternative materials. Improved wastewater treatment processes to capture microplastics before they enter aquatic environments are addressed. Biodegradable plastics and microplastic capture methods in wastewater treatment facilities are highlighted as promising green solutions. Green chemistry principles are emphasized throughout, highlighting the importance of environmentally friendly solutions. By implementing these strategies, we can significantly reduce microplastic pollution and protect our precious water resources.